PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR ASET DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Titi Aslah (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2020)
ABSTRACT This study aims to examine the effect of profitability, liquidity, asset structure, and company size on the capital structure of mining companies in the Indonesia Stock Exchange, in order to facilitate investors in investing. The research method used is a quantitative method using secondary data. The population in this study are coal mining companies listed on the Indonesia Stock Exchange from 2013-2017. The sample used was 18 companies using purposive sampling method, descriptive statistical data analysis techniques using Eviews Software. The results of this study indicate that profitability has no significant effect on capital structure, which is caused by the inability of the company to produce the maximum length of funds provided by shareholders, which means the company's financial performance is not good. Liquidity has a negative and significant effect on capital structure, where companies have abundant sources of funds, so companies are more likely to use internal funds to finance their investments. Asset structure has no positive effect but is not significant on capital structure, which means the higher the asset structure of a company the lower the company's ability to be able to guarantee long-term debt. The size of the company has a negative and significant effect on capital structure, which means that the larger the company, the greater the funds that will be issued both from their own capital and debt to maintain or develop the company.